A Constrained and "Inverted" [3+3] Salphen Macrocycle with an ortho‐Phenylethynyl Substitution Pattern. Issue 7 (23rd January 2020) - Urbani, Maxence; Torres, Tomas
Abstract: A [3+3] Schiff‐base salphen macrocycle (7 a ) was synthesized by imine condensation between ortho ‐phenylenediamine and ortho ‐phenylethynyl‐bridged bis(5‐salicylaldehyde) precursors. The triangular‐shaped macrocycle 7 a has a nonclassical (or "inverted") design in which the N2 O2 coordination pockets are located at the sides instead of the corners. Compound 7 a could be synthesized in a reasonably good yield (64 %) considering the steric constraints imposed by the ortho substitution pattern. Subsequent zinc metalation afforded the corresponding Zn metallomacrocycle 7 b . Spectroscopic experiments evidenced weak (7 a ) to strong (7 b ) self‐aggregation behavior in solution. Their ability to self‐organize at the supramolecular level was further studied in the solid state by AFM and TEM, which revealed the formation of large bundles of fibers with lengths of several micrometers and widths of nanometers. Abstract : Dark side of the triangle : The synthesis and supramolecular organization of a triangle‐shaped [3+3] salphen macrocyclic ligand in which the N2 O2 coordination pockets are located at the sides instead of the corners is reported. Both metal‐free and zinc‐metalated macrocycles self‐assemble to form nano‐ to micrometer‐sized fibers in the solid state.